Era Masyarakat Informasi - Moch Nurcholis Majid; Muh Usman (Al-Maquro' : Jurnal Komunikasi dan Penyiaran Islam, 2020)
Indonesian society is in the face of the transition to the era of the information society. In this process there is a shift in the pattern of society in using information technology. This is a lifestyle change that is a consequence of the use of information technology-based devices (ICT). The role of ICT technology in daily life cannot be separated, the ease of use is very helpful and also sometimes gives effect to dependence on daily work that is usually done by humans. Without realizing it, the speed and accuracy possessed in information and communication technology have a big influence, but how can we respond to the development of information technology even more so for people in Indonesia in the next 5 to 10 years. The use of information and communication technology in the implementation of the work system is getting better and better